2019
DOI: 10.1002/mrm.27962
|View full text |Cite
|
Sign up to set email alerts
|

Toward whole‐cortex enhancement with an ultrahigh dielectric constant helmet at 3T

Abstract: Purpose:To present a 3T brain imaging study using a conformal prototype helmet constructed with an ultra-high dielectric constant (uHDC; ε r ~ 1000) materials that can be inserted into standard receive head-coils. Methods: A helmet conformal to a standard human head constructed with uHDC materials was characterized through electromagnetic simulations and experimental work. The signal-to-noise ratio (SNR), transmit efficiency, and power deposition with the uHDC helmet inserted within a 20-channel head coil were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…A recent experimental study at 3 T showed an HPM cap having ε r of 1000 or greater within a commercial receive array provided great improvement in receive SNR selectively in the cortex, but with strong adverse distortion of the excitation field, 11 similar to results of simulations for a ε r of 200 shown here (Figure 3). From quasistatic approximations, achieving a similar effect at different frequencies with a given HPM and coil design should require an approximate relationship of ε r ∝ 1/ ω 2 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…A recent experimental study at 3 T showed an HPM cap having ε r of 1000 or greater within a commercial receive array provided great improvement in receive SNR selectively in the cortex, but with strong adverse distortion of the excitation field, 11 similar to results of simulations for a ε r of 200 shown here (Figure 3). From quasistatic approximations, achieving a similar effect at different frequencies with a given HPM and coil design should require an approximate relationship of ε r ∝ 1/ ω 2 .…”
Section: Discussionsupporting
confidence: 84%
“…28,29 Extrapolation of results shown here to 128 MHz (3 T) indicate ε r for optimal whole-brain improvement of transmit efficiency, and receive-array SNR may be closer to 500 or 600, and use of ε r of 1000 would result in effects like those reported. 11 The results presented here show the potential benefit for incorporating HPM into coil design for improving both transmit efficiency and receive array SNR for the entire brain at 7 T. The choices of coil and HPM geometry, and ε r of the HPM, all depend on the intended use of the array. Although this study includes a first experimental demonstration of advantages of incorporating HPM into a custom head receive array, we expect that further dedicated work in this area will result in further improvements.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…HDC materials have previously been used to enhance performances of standard commercial RF coils for lower magnetic fields 16–20 and 7 T with various geometrical shapes (flexible pads and rigid blocks) with different HDC materials (pure water, slurries, and ceramics) 21,22 . In recent efforts toward whole‐cortex enhancement, HDC helmets have been developed and demonstrated an overall increase in B1+ field and SNR in the human brain at 3 T and 7 T 23–25 .…”
Section: Introductionmentioning
confidence: 99%